2010
DOI: 10.1200/jco.2010.29.3597
|View full text |Cite
|
Sign up to set email alerts
|

Factors for Hematopoietic Toxicity of Carboplatin: Refining the Targeting of Carboplatin Systemic Exposure

Abstract: This study provides useful information to clinicians to better estimate the hematopoietic toxicity of carboplatin and thus choose more rationally carboplatin target AUCs as a function of pretreatment or concomitantly administered chemotherapies. For example, an AUC of 5 mg/mL · min is associated with a risk of grade 3 or 4 thrombocytopenia of 2% in combination with paclitaxel versus 38% with gemcitabine in a non-pretreated patient.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
42
2
1

Year Published

2015
2015
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 46 publications
(47 citation statements)
references
References 15 publications
2
42
2
1
Order By: Relevance
“…Since fewer TPO binding sites are available due to the low number of platelet counts induced by HIO, TPO increases and stimulates the proliferation of precursor cell, which ultimately will result in thrombocytosis (48). The magnitude of this feedback mechanism (0.621) is higher than the values reported in the literature for other anticancer agents (range 0.135 to 0.233) (49,52), probably because, after a major surgery, there is a further increase in circulating TPO due to its release from activated platelets (35).…”
Section: Discussioncontrasting
confidence: 50%
See 1 more Smart Citation
“…Since fewer TPO binding sites are available due to the low number of platelet counts induced by HIO, TPO increases and stimulates the proliferation of precursor cell, which ultimately will result in thrombocytosis (48). The magnitude of this feedback mechanism (0.621) is higher than the values reported in the literature for other anticancer agents (range 0.135 to 0.233) (49,52), probably because, after a major surgery, there is a further increase in circulating TPO due to its release from activated platelets (35).…”
Section: Discussioncontrasting
confidence: 50%
“…An estimated 47.5% reduction in k s suggested that the platelet lifespan increased from 3.23 days in nonsplenectomized patients to 7.78 days in splenectomized patients. The estimates of platelet lifespan in nonsplenectomized patients were lower than values previously reported, which ranged from 6 to 9 days in the absence of any surgical procedure (29,49,56). This difference is probably due to the increase in platelet destruction and consumption associated with the aggressive CRS treatment.…”
Section: Discussioncontrasting
confidence: 49%
“…The PK-PD modeling conducted on the 383 patients was based on the semimechanistic model of Friberg et al [17], to describe the relationships between carboplatin concentrations and absolute counts of neutrophils or platelets [6]. The principle of the Friberg model is to describe hematopoiesis by a succession of compartments: a proliferation compartment (for precursor cells), maturation compartments and a circulating compartment, related by rate constants which describe how the cells are transferred from one compartment to another.…”
Section: Studied Populationmentioning
confidence: 99%
“…The main eligibility criterion for the initial cohort was that the patient had to be treated with carboplatin as monotherapy or in combination with other chemotherapies such as paclitaxel, etoposide and gemcitabine, among others. [6]. From the 383 patients of the initial cohort, we only selected 201 patients who received carboplatin plus paclitaxel as chemotherapy and for whom DNA samples were available.…”
Section: Studied Populationmentioning
confidence: 99%
See 1 more Smart Citation